(untitled) (Applied Biological Research, 2023)
Zinc (Zn) is an important element in human biological system. Human autopsy wet tissues (67) of lungs and liver, collected at random from Ajmer population of Rajasthan (India), were analyzed for Zn content. The samples were taken from non-putrefied dead bodies received at JLN Medical College (JLNMC), Ajmer. The samples from human undergone death due to burn injury or drowning were not considered. Seven demographic data for each case were collected from their medical status reports (post-mortem report) and from the pathological and anatomical reports available at the Forensic Medicine Department, JLNMC and also from the relatives of sampled human cases. Fresh autopsy tissues were digested in di-acid and analyzed by graphite furnace atomic absorption spectrometry. In lungs and liver, the average Zn content was 26.4 and 46.1 µg g-1, respectively. The Zn content in lungs and liver samples varied from 11.59 to 97.51 and 26.63 to 114.29 µg g-1, respectively. In females the mean Zn levels were higher than males in both lung and liver. Rural residents had higher mean Zn content than peri-urban and urban residents. In occupation environment sub-group exposed to polluted area had low mean Zn content than non-exposed cases.